2015
DOI: 10.1002/jmv.24354
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms at IL28B gene as predictors of viral relapse in genotype 4 Egyptian hepatitis C patients

Abstract: Chronic HCV is one of the commonest causes of chronic liver disease worldwide with about 15% of population infected in Egypt. Certain single nucleotide polymorphisms (SNPs) lying near the IL28B gene were found to affect the spontaneous clearance as well as treatment outcome of HCV. To examine the association between different IL28B variants and the relapse of HCV infection after combined therapy with ribavirin and pegylated interferon (pegIFN). Hundered HCV genotype four patients received 1.5 mg/kg/week pegint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Furthermore, our results revealed that, TT genotype of IL-28B (rs8099917) was the most common in the studied patients (44.0%) while GT genotype identified in 42% and GG was detected in 14.0%. In agreement with our study, Ragheb et al (2014) and Esmail et al (2016) found that TT genotype was the most common among their studied patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, our results revealed that, TT genotype of IL-28B (rs8099917) was the most common in the studied patients (44.0%) while GT genotype identified in 42% and GG was detected in 14.0%. In agreement with our study, Ragheb et al (2014) and Esmail et al (2016) found that TT genotype was the most common among their studied patients.…”
Section: Discussionsupporting
confidence: 93%
“…Similar result was reported with Hendy et al regarding AST and ALT levels. On the other hand, Esmail et al (2016) detected no significant difference of ALT and AST with IL28B rs8099917 genotypes.…”
Section: Discussionmentioning
confidence: 70%
“…The most notable example in this regard is IL-28B, whose polymorphisms have been reported to associate with ETR. However, the available IL-28B data is still somewhat conflicting 41 42 and to date, no universally applicable predictive marker of PEG-INF/RBV therapy has been established. Due to the significance of miR-122 in HCV infections, the association between hepatic miR-122 expression and ETR has been evaluated in some recent reports.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, IL28B SNP, alpha fetoprotein level, and cytotoxic T-Lymphocytes antigen-4 (CTLA-4) SNP could be used in conjunction to predict treatment response in HCV-G4 infected Egyptian patients [30]. In addition, Esmail et al [31] demonstrated that IL-28B SNP polymorphism is considered as a vital predictor of viral relapse.…”
Section: Interleukin-28b Polymorphism Is a Pharmacogenetic Predictor mentioning
confidence: 99%